Relation Between New Culm Production and the Number of Old Culms in Bamboos and its Bearing on Rational Bamboo Management - Mathauda, G. S. (Indian Forester, 1960)
Comprehensive data about new culm production from clumps of different sizes for Dendrocalamus strictus, along with similar, though more limited, figures for a few other bamboo species in India are presented. The present practice of defining felling intensity in bamboo forests on the basis of last one or two season’s production is defective as the big fluctuations in new production are automatically reflected in the yields realised. It is explained that a rational method of control1ing bamboo fellings must be based on annual production averaged over a large number of years.